Results, Contributions, and Impacts After Eight Years of Forestry Projects Developed by INISEFOR in the Southern Region of Costa Rica - Barquero Elizondo, Ana Isabel (2018)
This paper presents an account of the work that the Universidad Nacional carried out in the forestry field in several counties of the southern part of Costa Rica. The paper aims to visualize how the results of the research, combined with teaching and production, constitute the base for a long-term university extension process. It was possible to collect data about the agricultural activities in the area and the existence of a forest value chain composed of several links; in these links, more than one hundred and fifty direct actors are integrated, only in the counties of Osa and Golfito. Due to the need for forest producers to have adequate genetic materials, a nursery and pilot plantations were established. The plantations work as demonstration fields for the farmers and play an important educational role in the training of forestry students of the Universidad Nacional. Due to the characteristics of the forestry activity, in this field university extension processes require an interdisciplinary approach and must be programmed in the long term, since trees need a more extended period for their growth and subsequent harvest, and the producers involved need to have complementarity with other activities, in order to achieve better living conditions.